Association between concomitant psychiatric drug use, and patients' beliefs about and persistence with chronic cardiovascular medication - Hromadkova, L; Heerdink, E R; Philbert, D; Bouvy, M L (International journal of clinical practice, 2015)
OBJECTIVE: Psychiatric disorders are associated with an increased risk of cardiovascular diseases and may result in additional risk of non-adherence. No data on the influence of concomitant psychiatric drug use on patients' beliefs and persistence related to cardiovascular medication are available. The objective of this study was to assess to what extent the use of concomitant psychiatric drugs is associated with patients' beliefs about and persistence with chronic cardiovascular medication. METHODS: An observational study in patients using cardiovascular medication was conducted. A mailed questionnaire containing socio-demographical questions and a measure of beliefs about medication (Beliefs about Medicines Questionnaire - specific) was sent to patients selected from fifteen participating pharmacies. Persistence was evaluated based on pharmacy records. RESULTS: Of the 1547 included patients, 551 responded to key questions in the questionnaire and were included for beliefs about medication analysis. In concomitant users of psychiatric drugs significantly higher necessity (17.0 vs. 16.0) and higher concerns (14.3 vs. 13.3), as well as higher proportion of ambivalent (34.5% vs. 25.6%) and lower proportion of indifferent patients (24.1% vs. 33.0%) were found compared with non-users (p < 0.05). 65.2% (n = 1009) of patients were persistent on all their cardiovascular drugs. There was no significant association between concomitant use of psychiatric drugs and non-persistence (OR = 1.2; 95% CI 0.9-1.5). CONCLUSION: Concomitant use of psychiatric drugs was found to be associated with increased beliefs about the necessity of and concerns about cardiovascular medication. Clinicians caring for cardiovascular patients should give additional attention to identifying patients' beliefs about medication among those concomitantly using psychiatric drugs.
Keywords: Surveys and Questionnaires; hodnocení adherence k farmakoterapii; kardiovaskulární nemoci; Humans; lidé středního věku; Female; Aged; mladý dospělý; dospělí; zdraví - znalosti, postoje, praxe; senioři; lidé; psychotické poruchy; Assessment of Medication Adherence; průzkumy a dotazníky; Adult; kardiovaskulární látky; antipsychotika; ženské pohlaví; Cardiovascular Diseases; Male; Middle Aged; Adolescent; Cross-Sectional Studies; Young Adult; Antipsychotic Agents; Cardiovascular Agents; Health Knowledge, Attitudes, Practice; mužské pohlaví; Psychotic Disorders; kombinovaná farmakoterapie; průřezové studie; Drug Therapy, Combination; mladiství